Perspektif Urban Public Transportation dalam Kajian Meta-Analysis - Sarjana, Sri (Department of Civil Engineering, Diponegoro University, 2021)
Urban public transportation is transportation system developed for the public interest that prioritizes the optimal integration of various resources and infrastructure in order to achieve sustainable city that is guided by green technology. The development of urban public transportation through scientific evolution that prioritizes the diversity of knowledge and technology as effort to create environmentally friendly city that is oriented towards sustainable development. Qualitative methods are applied in the analysis of themes studied by developing a meta-analysis. Primary data was obtained from the collection of scientific journals published from 1966 to 2020 as part the analysis of scientific literature. The results of study stated that there was significant increase in the number of papers and number of citations in last twenty years which indicated an improvement in knowledge development. There are several topics that have novelty that were found after an analysis on the theme of urban public transportation includes service quality, public space, transportation engineering, regulation, and bus rapid transit. For this reason, new topics found need to be followed up in further research in line with current technological developments.